Cluster randomised trials. - Barbui, C; Cipriani, A (2011)
Although randomised controlled trials are the reference methodology to assess the effects of therapeutic interventions, for interventions that naturally occur in groups of individuals random allocation of participants may be inappropriate. In these cases, the unit of random allocation may be the group or cluster, rather than the individual. Clinical trials that randomly allocate groups or clusters of individuals are called cluster randomised trials. This article briefly presents the main implications of cluster randomisation with respect to the following methodological aspects: generalisability, concealment of allocation, comparability at baseline, blindness, loss of clusters and intra-class correlation.